Tinjauan Hukum Terhadap Putusan Kasasi Mahkamah Agung Nomor 836K/PDT.SUS-HKI/2022 Mengenai Sengketa Merek Antara Starbucks Corporation Dan PT Sumatra Tobacco Trading Company - Sania Akalila Putri Thahir; Rika Ratna Permata; Ranti Fauza Mayana (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
The registration of trademarks with the “first to file” constitutive system, adopted by Indonesia, is often abused by trademark owners with malicious intent by first registering their trademarks that are similar to well-known trademarks, knowing that the well-known trademarks have not been registered in Indonesia. This was the case with the “Starbucks” trademark owned by Starbucks Corporation in Decision Number 836 K/Pdt.Sus-HKI/2022. Starbucks Corporation filed a lawsuit for the cancellation of “Starbucks” trademark in class 34 owned by Sumatra Tobacco Trading Company on the grounds of similarity to a well-known trademark for a different class and the malicious intent to exploit the reputation of the “Starbucks" trademark owned by Starbucks Corporation. The first lawsuit filed by Starbucks Corporation was rejected by the panel of judges, which led to Starbucks Corporation filing a cassation request. The research results indicates that the panel of judges in Decision Number 836 K/Pdt.Sus-HKI/2022 is in accordance with Law Number 20 of 2016 concerning Trademarks and Geographical Indications. The legal consequences for all parties involved in the trademark dispute after the decision are the cancellation of the "Starbucks" trademark owned by Sumatra Tobacco Trading Company from the General Register, the cessation of the use of the "Starbucks" trademark in class 34 by the cassation respondent, and the strengthening of the "Starbucks" trademark owned by the cassation applicant, with its status as a well-known trademark being affirmed.